Four contemporary novelists : Angus Wilson, Brian Moore, John Fowles, V.S. Naipaul - McSweeney, Kerry, 1941- (McGill-Queen's University Press, 1983)
Four Contemporary Novelists offer accounts of the fiction of Angus Wilson, Brian Moore, John Fowles, and V. S. Naipaul. The author has charted the development of each writer; identified dominant themes, controlling techniques, and informing sensibility; explained what each has tried to accomplish and compare theory to practice; provided an appropriate context for appreciation and evaluation of all parts of each canon; and made qualitative discriminations.